Integrating Augmented Reality with Management Information Systems for Enhanced Data Visualization in Retail - Ngr. Putu Raka Novandra Asta; Setiawan Setiawan; Memed Saputra; Najmuddin Najmuddin; Kddour Guettaoi Bedra (Journal of Social Science Utilizing Technology, 2024)
Background. Effective data management and visualization are essential for fast and informed decision-making in the retail industry. However, traditional data visualization methods are often less interactive and need help comprehensively conveying information. Augmented Reality (AR) offers great potential to improve visualizing data, allowing users to interact with data more intuitively and dynamically. Purpose. This research aims to integrate Augmented Reality technology with Management Information Systems (MIS) in retail, focusing on improving data visualization. The main objective is to evaluate the effectiveness of AR in presenting complex data more clearly and interactively to enhance the quality of decision-making in retail management. Method. The research method used is application development and testing. First, an AR application integrated with MIS is developed using an iterative software development approach. Once the application is created, testing is done in a retail environment. Qualitative and quantitative data were collected through observations, interviews, and surveys to evaluate the effectiveness and acceptability of this technology. Results. Research results show that integrating AR with MIS significantly improves how retail managers visualize and understand data. AR applications enable more interactive and easy-to-understand data visualization, which helps managers analyze trends and make better decisions. Users report improvements in decision-making efficiency and accuracy after using this app. Conclusion. Integration of Augmented Reality with Management Information Systems in retail has proven effective in improving data visualization. This technology not only makes data more accessible and understandable but also enhances user interaction with the data, leading to more informed decision-making. This research suggests a more comprehensive application of AR technology in the retail industry to support better and more efficient management.